Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1126/science.1122096
|View full text |Cite
|
Sign up to set email alerts
|

Rats Smell in Stereo

Abstract: It has been hypothesized that rats and other mammals can use stereo cues to localize odor sources, but there is limited behavioral evidence to support this hypothesis. We found that rats trained on an odor-localization task can localize odors accurately in one or two sniffs. Bilateral sampling was essential for accurate odor localization, with internasal intensity and timing differences as directional cues. If the stimulus arrived at the correct point of the respiration cycle, internasal timing differences as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
146
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 17 publications
9
146
0
1
Order By: Relevance
“…Similarly, we speculate that information about the right and left localization of odor sources detected by single-category E-I neurons in the AONpE may be transmitted to higher olfactory centers, in addition to the feedback connection to the contralateral OB. In agreement with this idea, behavioral studies have shown that rats can properly respond to odor localization cues (2,26). Single-cell labeling revealed that AONpE neurons send an axon collateral to AONpP (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Similarly, we speculate that information about the right and left localization of odor sources detected by single-category E-I neurons in the AONpE may be transmitted to higher olfactory centers, in addition to the feedback connection to the contralateral OB. In agreement with this idea, behavioral studies have shown that rats can properly respond to odor localization cues (2,26). Single-cell labeling revealed that AONpE neurons send an axon collateral to AONpP (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…For the directional localization of sound sources, the central auditory system has neuronal circuit mechanisms that compare auditory inputs from the right and left cochleas (1). Similarly, rodents can localize odor sources by comparing odor inputs through the right and left nostrils (2). However, the neuronal circuits and mechanisms subserving the right or left localization of odor sources are not yet known.…”
mentioning
confidence: 99%
“…In general, the sniffing behaviour observed here is highly dynamic 18,19 . Interestingly, the frequencies observed during odour tracking are much higher than the ~8 Hz observed during odour-based discriminations in morecontrolled odour sampling tasks in rats 15,18 . This higher 11-12-Hz sniffing has been observed in these previous studies but it occurred only during the period of reward anticipation.…”
Section: Rats Track Various Odour Trails Accuratelymentioning
confidence: 73%
“…The ability of animals to compare across two nostrils or antennae has been shown in various species, including rats, flies, humans and moths 12,[15][16][17] . However, it was not known if animals use this ability to track odours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation